Exploring the effect of wiki-based writing instruction on writing skills and writing self-efficacy of Chinese English-as-a-foreign language learners - Dai, Jianchun; Wang, Li; He, Yongcheng (Frontiers in Psychology, 2023)
As a popular Web 2.0 technology, wikis have gained momentum in educational contexts. To give further empirical support to the use of wikis in foreign language education, this research probed the usefulness of a wiki-based writing instruction on the writing skill and self-efficacy of Chinese English-as-a-foreign language (EFL) learners. For this purpose, 53 EFL students in a foreign language school in China were selected as the participants. The two classes were assigned to an experimental group (N = 25) and a control group (N = 28). Over a period of 3 months, the experimental group was instructed based on wiki-based writing instruction while the control group was taught traditionally. The data were collected by administering IELTS writing tasks and a writing self-efficacy scale employed for pre- and post-tests. The results of data analysis indicated that both classes substantially enhanced their writing skill and writing self-efficacy. Nevertheless, the experimental group performed better than the control group in terms of both dependent variables, leading the researchers to conclude that the wiki-based writing instruction was significantly effective in boosting writing skill and self-efficacy of Chinese EFL learners. These outcomes can offer some worthwhile implications for EFL instructors.